The 13th National Information Day: Open Science, Open Data, Open Access, Bulgarian Open Science Cloud - Stanchev, Peter; Karaivanova, Aneta; Zherkova, Yanita; Klisarova, Hristiyaniya; Pavlov, Radoslav; Simeonov, Georgi (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2022)
The paper gives an overview the current landscape and the activities on national and institutional level regarding Open Science, Open Access to scientific information, Open Data and the overall development of the BulgarianOpen Science Cloud.
Keywords: Open Access; Access to Knowledge; Open Science; European Open Science Cloud; Bulgarian Open Science Cloud